2022
DOI: 10.1093/jamia/ocac152
|View full text |Cite
|
Sign up to set email alerts
|

Impact of patient portal-based self-scheduling of diagnostic imaging studies on health disparities

Abstract: While many case studies have described the implementation of self-scheduling tools, which allow patients to schedule visits and imaging studies asynchronously online, none have explored the impact of self-scheduling on equitable access to care.1 Using an electronic health record patient portal, University of California San Francisco deployed a self-scheduling tool that allowed patients to self-schedule diagnostic imaging studies. We analyzed electronic health record data for the imaging modalities with the opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…were positively associated with both enrollment in and intent to use the patient portal. Research since 2020 has included differential use of self-scheduling aspects of the patient portal by race, ethnicity, and primary spoken language [33], and differential use by patients with chronic health conditions by age, gender, race, and ethnicity [8]. These individual level DDoH factors were consistently observed within our study and corroborate those reported previously.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…were positively associated with both enrollment in and intent to use the patient portal. Research since 2020 has included differential use of self-scheduling aspects of the patient portal by race, ethnicity, and primary spoken language [33], and differential use by patients with chronic health conditions by age, gender, race, and ethnicity [8]. These individual level DDoH factors were consistently observed within our study and corroborate those reported previously.…”
Section: Discussionsupporting
confidence: 88%
“…We observed that other patient factors, including being comfortable reading and speaking English, reported use of the internet to surf the web or to send or receive emails, having at-home internet access, and access to technology devices (computer, tablet, smartphone, etc), were positively associated with both enrollment in and intent to use the patient portal. Research since 2020 has included differential use of self-scheduling aspects of the patient portal by race, ethnicity, and primary spoken language [ 36 ], and differential use by patients with chronic health conditions by age, gender, race, and ethnicity [ 8 ]. These individual-level DDoH factors were consistently observed within this study and corroborate those reported previously.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the small sample size of our interview cohort increases the possibility of bias during the process of thematic analysis, particularly because we only interviewed 1 non-English speaker (using an interpreter, with the patient’s proxy present). Analyses from numerous implemented mHealth programs have shown that non-English speakers and patients of minority race or ethnicity are significantly less likely to engage in telemedicine [ 13 , 25 , 26 ]. Patient motivations for drop-off are nuanced and are likely strongly associated with sociocultural factors that can only be uncovered in larger, more diverse studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, work by Calixte noted that non-Hispanic Black individuals are less likely to fill prescriptions online compared to non-Hispanic Whites individuals ( 17 ). Similarly, an analysis by Ganeshan et al found that minoritized patients, non-English speaking, and Medicaid recipients were less likely to schedule appointments online ( 18 ).…”
Section: Discussionmentioning
confidence: 99%